Rethinking Openness in a Large-Scale ODeL Institution: How ICT Systems Integration Influence Transactional Distance and Student Equity in the Global South - Sevnarayan, Kershnee; Msomi, Thuthukani Vincent (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance, 2026)
This research article presents a unique contribution to the existing body of knowledge as it examines the concept of openness within an open distance e-learning (ODeL) institution in South Africa, through the lens of Moore’s theory of transactional distance. As one of the world’s largest ODeL providers, which serves over 400,000 students annually, the institution embodies both the promise and perils of scaling distance education in the Global South. The study focuses on the integration of information and communication technology (ICT) systems and investigates how such integration either reduces or exacerbates transactional distance, which may enable or constrain openness. The theory is guided by three core elements: dialogue, structure, and autonomy. The research explores stakeholder perspectives to understand how ICT systems influence equitable access, meaningful interaction, and learner agency. Specifically, the research seeks to understand how integration processes for ICT systems can be managed to promote openness and contribute to student success. In addition, the study explores the viewpoints of lecturers, students, and the ICT personnel on openness within the institution. This qualitative research approach involves data collection through email interviews, focus group discussions, and evaluation questions. The findings reveal that true openness in ODeL is not guaranteed by digital delivery alone but depends on deliberate efforts to reduce transactional distance through reliable infrastructure, inclusive design, and responsive support. These findings have implications for educational institutions and prompt a review of distance learning strategies to enhance relevance, adapt to technological advancements, and encourage a conducive open distance teaching and learning context.